1999
DOI: 10.1083/jcb.144.6.1295
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Changes in Integrin and Focal Adhesion Signaling Regulate Myoblast Cell Cycle Withdrawal

Abstract: We previously demonstrated contrasting roles for integrin α subunits and their cytoplasmic domains in controlling cell cycle withdrawal and the onset of terminal differentiation (Sastry, S., M. Lakonishok, D. Thomas, J. Muschler, and A.F. Horwitz. 1996. J. Cell Biol. 133:169–184). Ectopic expression of the integrin α5 or α6A subunit in primary quail myoblasts either decreases or enhances the probability of cell cycle withdrawal, respectively. In this study, we addressed the mechanisms by which changes in integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
138
2
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(152 citation statements)
references
References 97 publications
10
138
2
2
Order By: Relevance
“…In our experiments, we found similar levels of paxillin in the malignant astrocytoma cells plated onto ®bronectin, laminin, or vitronectin for 5 h. Thus, although our experiments are not directly comparable to those reported in myoblasts (Sastry et al, 1999), our data demonstrate that engagement of the a5b1 integrin by plating on a ®bronectin substrate does not in itself result in increased paxillin protein expression in U-251MG cells, as compared to engagement of the a6b1 laminin receptor integrin and the avb3/avb5 vitronectin receptor integrins. However, our data do suggest that there is a cooperation of TGF-b1 with the a5b1 ®bronectin receptor integrin in the malignant astrocytoma cells, as TGF-b1 failed to increase the expression of paxillin protein when the cells were plated onto other substrates (laminin, collagen, or vitronectin).…”
Section: Discussioncontrasting
confidence: 36%
See 1 more Smart Citation
“…In our experiments, we found similar levels of paxillin in the malignant astrocytoma cells plated onto ®bronectin, laminin, or vitronectin for 5 h. Thus, although our experiments are not directly comparable to those reported in myoblasts (Sastry et al, 1999), our data demonstrate that engagement of the a5b1 integrin by plating on a ®bronectin substrate does not in itself result in increased paxillin protein expression in U-251MG cells, as compared to engagement of the a6b1 laminin receptor integrin and the avb3/avb5 vitronectin receptor integrins. However, our data do suggest that there is a cooperation of TGF-b1 with the a5b1 ®bronectin receptor integrin in the malignant astrocytoma cells, as TGF-b1 failed to increase the expression of paxillin protein when the cells were plated onto other substrates (laminin, collagen, or vitronectin).…”
Section: Discussioncontrasting
confidence: 36%
“…Other investigators have reported previously that transfection of the a5 subunit of the ®bronectin receptor integrin into myoblasts promoted cell proliferation and increased paxillin protein expression (Sastry et al, 1999). In our experiments, we found similar levels of paxillin in the malignant astrocytoma cells plated onto ®bronectin, laminin, or vitronectin for 5 h. Thus, although our experiments are not directly comparable to those reported in myoblasts (Sastry et al, 1999), our data demonstrate that engagement of the a5b1 integrin by plating on a ®bronectin substrate does not in itself result in increased paxillin protein expression in U-251MG cells, as compared to engagement of the a6b1 laminin receptor integrin and the avb3/avb5 vitronectin receptor integrins.…”
Section: Discussionmentioning
confidence: 99%
“…Forced overexpression of paxillin in cultured quail myoblasts blocks differentiation, instead promoting continued cell proliferation and signaling through the MAP kinase pathway (227). Phosphorylation of paxillin on amino acids Y31/118 and S188/190, which have each been shown to be regulated via integrin signaling, is necessary to maintain the undifferentiated phenotype (227).…”
Section: Integrin-actin Linkages and Muscle Contractionmentioning
confidence: 99%
“…In vitro studies have shown that ␣6␤1 is able to inhibit proliferation and stimulate differentiation of myoblasts (Sastry et al, 1996(Sastry et al, , 1999 and laminin promotes myoblast differentiation in vitro, inducing them to become postmitotic, fusion-capable, and myosin-and desmin-positive (von der Mark and Ocalan, 1989). In fact, it has been demonstrated recently that the ECM is necessary for skeletal muscle differentiation, independently of MRF expression, suggesting that, upon binding to the ECM, integrins generate signals that drive skeletal muscle differentiation (Osses and Brandan, 2002).…”
Section: Laminin Receptor ␣6␤1 In Epaxial Myotome Formationmentioning
confidence: 99%